The Role of Proteasome Inhibitors in Treating Acute Lymphoblastic Leukaemia - Sin, Chun-fung; Man, Pui-hei Marcus (Frontiers in Oncology, 2021)
Acute lymphoblastic leukaemia (ALL) is an aggressive haematolymphoid malignancy. The prognosis of ALL is excellent in paediatric population, however the outcome of relapse/refractory disease is dismal. Adult ALL has less favourable prognosis and relapse/refractory disease is not uncommonly encountered. Bortezomib is the first generation proteasome inhibitor (PI) licensed to treat plasma cell myeloma and mantle cell lymphoma with favourable side effect profile. Efficacy of bortezomib had been proved in other solid tumors. Clinical studies showed promising response for PIs in treating relapse/refractory ALL. Thus, PIs are attractive alternative agents for research in treating ALL. In the review article, we will introduce different proteasome inhibitors and their difference in pharmacological properties. Moreover, the mechanism of action of PIs on ALL will be highlighted. Finally, results of various clinical studies on PIs in both paediatric and adult ALL will be discussed. This review article provides the insights on the use of PIs in treating ALL with a summary of mechanism of action in ALL which facilitates future research on its use to improve the outcome of ALL.